GEOMETRIC EVALUATION OF COMPLEX CAVITY INTRUDED IN HEAT GENERATED WALLS - Guimaraes, M. V. F.; Emmendorfer, L. R.; Prolo Filho, J. F.; Santos, E. D. dos (Revista de Engenharia Térmica, 2017)
In this work it is presented a numerical study about geometrical evaluation of heat transfer in solids with volumetric heat generation and complex intruded cavity for cooling the wall by means of Constructal Design. Several cavities with varied shapes have been evaluated in literature, such as I-, T- and H-shaped cavities. The purpose here is to evaluate a complex cavity that combines different elemental shapes. More precisely, the resultant cavity is a merge between a H-shaped cavity and a I-shaped one, forming a ramified geometry, which is more expected in the flow between a point and volume in systems with high magnitude. The main purpose is to minimize two times the maximal temperature in the solid domain (Tmax). Here two degrees of freedom are defined for the cavity: H1/L1 (ratio between the second branch thickness and its length) and H0/L0 (ratio between the third branch height and its thickness) and the area of cavity is the constraint. For each geometrical configuration the heat diffusion equation is solved with the Finite Element Method (FEM). Results showed that differences of until five times between the optimal shapes and the worst ones are achieved, showing the importance of application of Constructal Design in the problem. Moreover, the best performance is achieved when the vertical branches are fully intruded in the solid domain for intermediate lengths of horizontal branch.